(untitled) - Nguyễn, Thị Cẩm Tiên (Cần Thơ, 2020)
This study aims to investigate EFL students’ perspectives on conditions for their developing intercultural communicative competence in learning foreign language. The research was conducted on 129 students at Can Tho University. The research instruments were employed including the questionnaire and the structured interview. The current research is conducted because English major students seem to feel less confident to communicate with foreigners or their partners after graduation. The results from the study revealed that most of students understood the definition of intercultural communicative competence (ICC), and they present that conditions for developing ICC for English majored students were necessary and indispensable.
Keywords: Anh ngữ,English language; Dạy và học,Study and teaching